PENERAPAN KONSELING RASIONAL EMOTIVE THERAPY UNTUK MENGATASI KECEMASAN DALAM PELAKSANAAN UJIAN AKHIR SEMESTER - Handayani, Putri; Sumarwiyah, Sumarwiyah; Gudnanto, Gudnanto (Universitas Muria Kudus, 2023)
This study aims: 1. Knowing the factors that cause anxiety in the implementation of the final semester exam, 2. Overcoming anxiety in the implementation of the final semester exam using rational emotive therapy (RET) counseling. The subjects studied were 2 students of class XII-MIPA 5 SMA N 01 Jekulo Kudus. Data collection methods using observation, interviews, and documentation methods conducted in depth. Based on this case, the counselee faced problems in facing the final semester exam, because he was afraid when doing the questions, nervous, dizzy, forgot / blank when doing the questions, lack of concentration, and fear of competing grades in class. Providing rational emotive therapy counseling, the counselee changed his way of thinking so as to produce meaningful changes in the way he feels and feels. and behavior, and can accept that one's success lies in individual self-confidence and not just because of test scores.